Professional Development and Coaching of Educators and Education Personnel - Nurul Zaman (Journal of Islamic Education El Madani, 2026)
This study aims to see and analyze the Professional Development and Guidance of Educators and Education Personnel. The research method used in this study is to use the literature study method by collecting literature (material materials) sourced from various journals and books written by people who understand and discuss the administration of educators and education personnel. After the literature materials sourced from journals and books were collected, this article was compiled by combining all the literature obtained that was in accordance with educational administration, especially the administration of educators and education personnel which are very related. The results of this study are that the professional development and guidance of PTK is carried out based on the needs of institutions, groups, or individual educators. teacher professional development models, including: (1) conference participation, (2) workshops and in-service seminars, (3) reading groups, (4) peer observation, (5) writing teaching diaries/journals, (6) project work, (7) classroom action research, (8) teaching portfolio, and (9) Kennedy stated that there are nine models of teacher professional development, namely: (1) training model, (2) award-bearing model, (3) deficit model, (4) cascade model, (5) standards-based model, (6) coaching/mentoring model, (7) community of practice model, (8) action research model, (9) transformative model. Each has characteristics that are tailored to the needs of teachers. The challenge in developing PTK is the lack of facilities and human resources that are able to adapt to the times. The Role and Function of LPTK in Building Professional PTK is to prepare Educators and Education Personnel. The Implementation of the PTK Development and Coaching Program is carried out at all institutions or schools at every level. The implications of this research indicate that professional development and coaching for educators and education personnel (PTK) must be implemented systematically, sustainably, and based on the actual needs of both institutions and individual educators. The diversity of established professional development models confirms that no single approach is most effective for all contexts, so educational institutions need to implement flexible and adaptive strategies tailored to teacher characteristics and the work environment.